(untitled) (Bangladesh Journal of Microbiology, 2008)
The present study was performed to evaluate the microbiological quality of industrially processed packed juices such as mango, orange and lemon of five different local companies. Aerobic plate count (APC) in juice samples was nil when measured before and after neutralization of pH. However, after enrichment of couple of samples growth of bacteria was observed on nutrient agar and MacConkey agar media. Sample A showed 120 cfu/ml after 3 h on nutrient agar and 20 cfu/ml after 5 h on MacConkey agar medium. These findings indicate that manufacturers might use high amount of preservatives that had bacteriostatic effect on microbes. It can be suggested that processed juices should be prepared under hygienic condition without use of high amount of preservatives that might cause health hazard. Keywords: Fruit juice, Bacterial count, Preservatives, Enrichment DOI: http://dx.doi.org/10.3329/bjm.v24i2.1267